COMPARATIVE STUDY OF ECOLOGICAL GROUPS OF HIPPOHAE RHAMNOIDES PHYTONEMATOIDS GROWING IN THE ZARAFSHAN OASIS - K.S.Boltaev; A.N. Mamedov (Galaxy International Interdisciplinary Research Journal, 2021)
As a result of the study of nematodes of the dwarf retail plant growing in the tugai forests of Akdarya and Karadarya oases and Jambay reserve, 88 species of phytonematodes belonging to 6 genera, 28 families and genera were identified. A comparison of nematodes derived from the root and peripheral soil of this plant revealed that 65 species of nematodes were associated with the peripheral soil and 46 species with the rhizome.